Representations of masculinity in African women’s literature and their implications for English FET education: A feminist study of Ama Ata Aidoo’s Changes: A love story, Chimamanda Ngozi Adichie’s Purple Hibiscus and Sindiwe Magona’s Mother to Mother - Mohlala, Morufane Relebogile (University of the Witwatersrand, Johannesburg, 2024)
Masculinity is a socially constructed concept that prescribes certain behaviours and attitudes which are deemed acceptable for ‘real’ men. How an individual embodies or performs his masculinity is usually in relation to those around him and how they embody their own masculinities or femininities as well. This dissertation seeks to re-interrogate the representations of masculinity in Ama Ata Aidoo’s Changes: A Love Story, Chimamanda Ngozi Adichie’s Purple Hibiscus and Sindiwe Magona’s Mother to Mother. It seeks to analyse the various forms of masculinity emerging from these three novels which have been prescribed novels in schools in South Africa, and to discuss the implications of these representations on English FET education. Using an African feminist analysis of the novel and an application of the African feminist conceptualisation of masculinities, the analysis of the three novels reveals three factors. In Ama Ata Aidoo’s Changes: A Love Story, the analysis reveals that Aidoo is guilty of only rewriting the conditions of her central female character Esi, while her other two female characters’ conditions remain unchanged, as a result of the problematic masculinities enacted by the men in their lives. In Chimamanda Ngozi Adichie’s Purple Hibiscus, the analysis reveals that Adichie can be given some credit as she introduces an alternate form of masculinity that is inspiring; however, Adichie still focuses on the problematic and un-transforming masculinity of her central male character and makes the transforming masculinity a secondary character. In Sindiwe Magona’s Mother to Mother, the analysis reveals that Magona makes a significant attempt at theorising the violent and violating masculinities that are found in South Africa. From the analyses of the three novels, this study identifies a gap that presents itself between the intended purpose of literature and the rudimentary way in which it is actually approached in South African English classrooms. To try and bridge this gap, I recommend the use of an African critical masculinity pedagogy to help teach these novels in critical ways that will move learners understand the nuanced meanings of masculinity.
A research report Submitted in fulfillment of the requirements for a Master of Education, In the Faculty of Humanities , Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; African feminism; African critical masculinity pedagogy; African literature; African masculinities; African women writers; critical pedagogy; English FET education; masculinity; teaching masculinities; SDG-4: Quality education